Outcomes following Peripheral Nerve Decompression with and without Associated Double Crush Syndrome: A Case Control Study. Issue 1 (January 2017) - Wessel, Lauren E.; Fufa, Duretti T.; Canham, R. Bruce; La Bore, Adam; Boyer, Martin I.; Calfee, Ryan P.
Abstract : Background: Double crush syndrome, the association between proximal and distal nerve lesions, has been established. This investigation compares the outcomes of nerve surgery in patients with isolated peripheral compression versus those with double crush syndrome treated with peripheral nerve and cervical spine operations. Methods: This case-controlled study enrolled 80 patients: 40 underwent carpal or cubital tunnel surgery and cervical spine surgery (double crush group); and 40 controls, matched by age and sex, underwent only peripheral nerve decompression (peripheral nerve group). A minimum of 18 months was required after peripheral nerve and cervical spine surgery for office assessment (mean, 4.9 years and 6.0 years, respectively). Statistical analysis compared postoperative function and symptom severity questionnaires, physical examination, and patient-reported satisfaction between groups. Results: Patients in the double crush group reported significantly more disability and persistent symptoms on the QuickDASH questionnaire (29 versus 13) and Levine Katz symptom severity (2.0 versus 1.4) and functional status scales (1.9 versus 1.4). Double crush patients reported significantly lower satisfaction. The double crush group exhibited a greater frequency of persistent signs of nerve irritability and muscle weakness compared with the control group. Conclusions: At a minimum of 18 months after peripheral nerve surgery, patients with a history of cervical spine surgery are likely to have inferior patient-reported outcomes, persistent nerve dysfunction, and lower satisfaction after peripheral nerve release compared with patients following isolated peripheral nerve surgery. Double crush syndrome was associated with poorer outcome after peripheral nerve surgery despite treatment of cervical spine nerve compression. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.